Carrier Transport mechanisms contributing to the sub-threshold current in 3C-SiC-on-Si Schottky Barrier Diodes - Arvanitopoulos, A.; Perkins, Samuel; Gyftakis, K. N.; Lophitis, Neophytos; Jennings, M. R.; Antoniou, Marina (My University, 2018)
3C-Silicon Carbide (3C-SiC) Schottky Barrier Diodes on silicon (Si) substrates (3C-SiC-on-Si) seem not to comply with the superior wide band gap expectations in terms of excessive measured sub-threshold current. In turn, that is one of the factors which deters their commercialization. Interestingly, the forward biased part of the Current-Voltage (I-V) characteristics in these devices carries considerable information about the material quality. In this context, an advanced Technology Computer Aided Design (TCAD) model for a vertical Platinum/3C-SiC Schottky power diode is created and validated with measured data. The model includes defects originating from both the Schottky contact and the hetero-interface of 3C-SiC with Si which allows the investigation of their impact on the magnification of the sub-threshold current. For this, barrier lowering, quantum field emission and trap assisted tunneling of majority carriers need to be considered at the non-ideal Schottky interface. The simulation results and measured data allowed for the comprehensive characterization of the defects affecting the carrier transport mechanisms of the forward biased 3C-SiC on Si power rectifier for the first time.
Keywords: 3C-SiC; band diagram; carrier transport; defects; heteroepitaxy; SBD; Schottky interface; TCAD; unipolar